Advancing food, nutrition, and health research in Europe by connecting and building research infrastructures in a DISH-RI: Results of the EuroDISH project. (March 2018) - Snoek, Harriëtte M.; Eijssen, Lars M.T.; Geurts, Marjolein; Vors, Cecile; Brown, Kerry A.; Bogaardt, Marc-Jeroen; Dhonukshe-Rutten, Rosalie A.M.; Evelo, Chris T.; Fezeu, Leopold K.; Finglas, Paul M.; Laville, Martine; Ocké, Marga; et al.
Abstract: Background: Research infrastructures (RIs) are essential to advance research on the relationship between food, nutrition, and health. RIs will facilitate innovation and allow insights at the systems level which are required to design (public health) strategies that will address societal challenges more effectively. Approach: In the EuroDISH project we mapped existing RIs in the food and health area in Europe, identified outstanding needs, and synthesised this into a conceptual design of a pan-European DISH-RI. The DISH model was used to describe and structure the research area: D eterminants of food choice, I ntake of foods and nutrients, S tatus and functional markers of nutritional health, and H ealth and disease risk. Key findings: The need to develop RIs in the food and health domain clearly emerged from the EuroDISH project. It showed the necessity for a unique interdisciplinary and multi-stakeholder RI that overarches the research domains. A DISH-RI should bringservices to the research community that facilitate network and community building and provide access to standardised, interoperable, and innovativedata andtools . It should fulfil the scientific needs to connect within and between research domains and make use of current initiatives. Added value can also be created by providing services to policy makers and industry, unlocking data and enabling valorisation of research insights in practice through public-private partnerships. The governance of these services (e.g. ownership) and the centralised and distributed activities of the RI itself (e.g. flexibility, innovation) needs to be organised and aligned with the different interests of public and private partners. Highlights: EuroDISH showed the need for a unique, overarching RI in the food & health domain. The RI should connect countries and research disciplines, and build on existing RIs. It should provideservices that facilitate research network and community building. It should provide access to standardised, interoperable, innovativedata andtools . And, it should serve researchers, policy makers, industry, and societal stakeholders.